First Molecular Characterisation of Blastocystis from Experimental Rats in Turkey and Comparison of the Frequencies Between Obese and Non-obese Groups - Erdoğan Malatyalı; Gizem Başaran; Alpaslan Gökçimen; Hatice Ertabaklar; Sema Ertuğ (Türkiye Parazitoloji Dergisi, 2021)

(untitled)
Objective:Blastocystis is a zoonotic protozoan that infects a wide range of animals, including humans and rodents. This study aimed to determine the frequency and subtype distribution of Blastocystis in laboratory rats at a laboratory animal facility in Turkey.Methods:This study included 54 male Sprague-Dawley rats from Aydın Adnan Menderes University Laboratory Animal Center. Among these rats, 30 were fed with high-fat diet (obese group) and the remaining 24 received standard chow (non-obese group). Blastocystis positivity was determined with amplification of small subunit 18S rRNA gene following their nucleic acid extraction from faecal samples. Subtypes were detected by submitting the partial 18S rRNA gene sequences to the database (pubmlst.Results:Blastocystis infection was detected in 33 (61.1%) of 54 laboratory rats. The frequency of Blastocystis was significantly different between obese and non-obese rats (p<0.05), with 43.3% and 83.3%, respectively. When referred to the database, exact matches were identified with Blastocystis subtype 4 (ST4) for all isolates. In the phylogenetic analysis of the partial 18S rDNA sequence, the sequence was closely clustered with reference ST4 subtypes from other countries, including China, Japan, United Kingdom and Czech Republic.Conclusion:This study revealed the high rate of Blastocystis colonisation in laboratory rats, posing a risk for human transmission. The comparison of obese and non-obese groups supported the idea that Blastocystis might be an indicator of healthy gut flora. The detection of ST4 in all rats agreed with previous reports of the predominance of this subtype in rodents.